Subclinical dysfunction of remote myocardium is related to high NT-proBNP and affects global contractility at follow-up, independently of infarct area - Diana, Giovanni; Locorotondo, Gabriella; Manfredonia, Laura; Graziani, Francesca; Lombardo, Antonella; Lanza, Gaetano Antonio; Pedicino, Daniela; Liuzzo, Giovanna; Massetti, Massimo; Crea, Filippo (Frontiers in Cardiovascular Medicine, 2022)
Background. In ST-segment elevation myocardial infarction (STEMI), predictors of subclinical dysfunction of remote myocardium are unknown. We prospectively aimed at identifying clinical and biochemical correlates of remote subclinical dysfunction and its impact on left ventricular ejection fraction (LVEF). Methods. One-hundred thirty-three patients (63.9±12.1 years, 68% male) with first successfully treated (54% anterior, 46% non-anterior, p=0.19) STEMI underwent echocardiography at 5±2 days after onset and at 8±2-month follow-up, and were compared to 13 age and sex-matched (63.3±11.4) healthy controls. All 16 left ventricular (LV) segments were grouped into ischemic, border and remote myocardium: mean value of longitudinal strain (LS) within grouped segments were expressed as iLS, bLS, rLS, respectively. LV end-diastolic, end-systolic volumes indexed for body surface area (EDVi, ESVi, respectively), LVEF and global LS (GLS) were determined. Creatinine, glomerular filtration rate, admission level of NT-pro-brain-natriuretic peptide (NT-proBNP) and troponin peaks were considered for the analysis. Results. At baseline, rLS (15.5±4.4) was better than iLS (12.9±4.8, p<0.001), but lower than that in controls (19.1±2.7, p<0.001) and similar to bLS (15±5.4, p=ns), and did not differ between patients with single or multivessel coronary artery disease (CAD). At multivariate regression analysis, only admission NT-proBNP levels but not peak Tn levels independently predicted rLS (β= -0.58, p=0.001), as well as iLS (β= -0.52, p=0.001). Both at baseline and at follow-up, rLS correlated to LVEF similarly to iLS and bLS (p<0.001 for all). Median value of rLS at baseline was 15%: compared to patients with rLS≥15% at baseline, patients with rLS<15% showed lower LVEF (52.3±9.4 vs 58.6±7.6, p<0.001) and GLS (16.3±3.9 vs 19.9±3.2), and higher EDVi (62.3±19.9 vs 54±12, p=0.009) and ESVi (30.6±15.5 vs 22.3±7.6, p<0.001) at follow-up. Conclusion. In optimally treated STEMI, dysfunction of remote myocardium assessed by LS: 1) is predicted by elevated NT-proBNP; 2) is independent of CAD extent and infarct size; 3) is associated to worse LV morphological and functional indexes at follow-up